Rekonstruksi teori maslahah dan signifikansinya dalam pengembangan ekonomi Islam - Agus Waluyo Nur (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
The article traces to find the significance of maslahah to solve Islamic economics problems in the ageof globalization. The age of globalization supported by information technologies revolution makes allaspects of human life changes rapidly especially in economic activities. Islamic economic developmentrequired ijtihad with respect to the reality. In the context of ijtihad, Islamic economic require to be wokeup in the frame of maqasid shari‘ah. Maslahah, as important part of maqasid, need to be placed proportion-ally. Benefit, maslahah, and benediction (falah) will be reached only if Islamic values and principles areimplemented in the economic behavior. Neglecting to one of them will make it cripple. Applycation ofeconomic principles without Islamic values will only give material benefit, while principal execution andvalue will bear benediction and benefit or maslahah eternity world. Therefore consumer whose applyingsufficiency principle in buying goods, will buy goods so that minimum requirement of him fufilled. Hewill sought to fulfill the requirement without require to look into the availibility of goods to others. Onthe contrary if only executed principle, hence it will yield earthly benefit.